Time restriction aspects in the modeling of cyber-physical systems for industry 4.0 - Lizárraga, M. L.; Buelna, A.; Díaz-Ramirez, A.; Amaro-Ortega, V.; Kostikova, M. V.; González-Navarro, F. F.; Werner, F.; Burtseva, L. (Харьковский национальный автомобильно-дорожный университет, 2018)
Cyber-physical systems in Industry 4.0 are comprised of a computational core, a communication core, and a physical system. The computational core has strict timing restrictions and represents a Real-time system. In this paper, the modeling of the computational core is discussed.
Keywords: Real-time system; Cyber-physical system; Scheduling, Industry 4.0; Earliest Deadline First policy; Rate Monotonic policy; 004.415+004.94